Sangguniang Kabataan handbook for New Youth Councils - Abletez, Jose P. (Mary Jo Pub., 1992)
It is about the Sangguniang Kabataan (SK) as a council the of youth in every barangay. It is intended to teach the youth the basics of organizational development and leadership training. SK throughout the country must be well versed on the Local Government Code and the role they and their councils and federations must play.